2019
DOI: 10.37190/epe190406
|View full text |Cite
|
Sign up to set email alerts
|

Significant waste properties in terms of applicability in the power industry

Abstract: The aim of the article is to present the physical and chemical properties of the refuse derived fuel (RDF) substrates, which have a significant impact on the energy recovery process in power plants. The experimental part includes technical (moisture and ash content, net and gross calorific values) and elemental analyses (sulfur, chlorine and mercury content), biomass and non-biomass concentration in the samples. In order to carry out the analysis of reactor slagging and fouling risk, chemical composition of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Each 10% increase in the share of heat from RDF 1 saves 3.2 Mg of coal per hour, which gives a financial profit of EUR 213 (see Figure 4). In the work by [40], the mass saving of the coal with the assumption of 30% RDF combustion was equal to 3 Mg per hour. The savings due to lower coal consumption were calculated by assuming that the purchase cost of fossil fuel substituted with RDF is EUR 67 per 1 Mg [52].…”
Section: Materials and Economic Balancementioning
confidence: 99%
See 1 more Smart Citation
“…Each 10% increase in the share of heat from RDF 1 saves 3.2 Mg of coal per hour, which gives a financial profit of EUR 213 (see Figure 4). In the work by [40], the mass saving of the coal with the assumption of 30% RDF combustion was equal to 3 Mg per hour. The savings due to lower coal consumption were calculated by assuming that the purchase cost of fossil fuel substituted with RDF is EUR 67 per 1 Mg [52].…”
Section: Materials and Economic Balancementioning
confidence: 99%
“…Den Boer and Jędrczak [39] performed an analysis of the waste input from a mechanical-biological treatment plant in Poland, and detected that the share of biodegradable fractions changed (from 39 to 95%) depending on the size fraction of the studied materials. Nowak et al [40] found that the concentration of the biodegradable fraction in waste samples classified with 12-19 varied from 25 to 45%. The lowest values were obtained for waste materials with the ash amount of 70% w/w.…”
Section: Introductionmentioning
confidence: 99%
“…It should be taken into account that the production of RDF is one of the waste-to-energy strategies whose goal is to solve both waste and energy problems. Thus RDF can be utilized for energy recovery in direct combustion or co-combustion systems in cement plants, paper, and pulp mills, heat and power plants as well as incineration plants [23].…”
Section: Current Situation In Municipal Solid Waste Managementmentioning
confidence: 99%